A Study of the Influences of Organizational Culture towards Employee Engagement for Operational Staff in an Industrial Estate in Rayong Province - ธมั่นคง, มลฤทัย; วัฒนาทรงยศ, พิมพ์ปวีณ์; อิงอาจ, อภิญญา (KKBS Journal of Business Administration and Accountancy, 2017)
This research aimed to determine 1) The level of perception for organizational culture and employee engagement of operational staff in an industrial estate in Rayong 2) The influences of organizational culture towards employee engagement perceived by operational staff in an industrial estate in Rayong and 3) To study the invariance of the influences of organizational culture towards employee engagement perceived by operational staff working for management with four different nationalities in an industrial estate in Rayong. Sampling is a group of operational staff who worked in an industrial estate in Rayong amounting 400 people who worked for management with four different nationalities. Quota Sampling was applied, together with application of research tool by questionnaire rating scale based on the four-level Likert with the level of confidence in between 0.83-0.96. The applied statistics Frequency, Percentage, Mean, Standard deviation, Pearson’s Correlation and Structural Equation Modeling testing. The research results showed that: 1. Operational staff who worked in an industrial estate in Rayong perceived organizational culture and employee engagement at a rather much level 2. The level of perceived organizational culture had positive influences towards employee engagement for operational staff in an industrial estate in Rayong. 3. Hypothesis testing found that the model of influences for perceived organizational culture towards employee engagement for operational staffs in an industrial estate were different as per nationalities of management. The results of this study were to facilitate strategic human resources management by integrating organizational culture and employee engagement cultivation.